Combined Lifestyle and Air Pollution Drivers of Liver Injury: A Literature Review - Amalia Arum Permatasari (Journal of Social Research, 2026)
This literature review aimed to summarize recent studies regarding the combined effects of unhealthy lifestyle behaviors and air pollution exposure on the development and progression of metabolic dysfunction-associated steatotic liver disease (MASLD). A literature search was conducted using the ScienceDirect and PubMed databases from December 2025 onward. Relevant studies examining the relationship between air pollution, lifestyle factors, and MASLD or hepatic injury were identified using Medical Subject Headings (MeSH) terms and free-text keywords related to MASLD, particulate matter (PM?.?), unhealthy lifestyle behaviors, inflammation, oxidative stress, and metabolic dysfunction. Eligible articles included original research and review articles published in English that investigated hepatic outcomes associated with lifestyle factors and/or particulate matter exposure. Evidence indicates that both particulate matter exposure and lifestyle-related factors, including unhealthy dietary patterns, sedentary behavior, smoking, alcohol consumption, and circadian rhythm disruption, independently contribute to liver injury through shared biological mechanisms. These mechanisms include inflammation, oxidative stress, insulin resistance, mitochondrial dysfunction, and gut dysbiosis. Exposure to PM?.? promotes reactive oxygen species (ROS) generation, activation of Kupffer cells (KCs), stimulation of hepatic stellate cells (HSCs), and the release of pro-inflammatory cytokines. Meanwhile, unhealthy lifestyle behaviors contribute to metabolic imbalance and impaired antioxidant defense mechanisms. Emerging evidence suggests that the coexistence of high air pollution exposure and unhealthy lifestyle patterns produces synergistic effects that accelerate hepatic steatosis, inflammation, fibrosis, and progression toward MASLD. The combined effects of prolonged particulate matter exposure and unhealthy lifestyle behaviors represent important and underrecognized contributors to MASLD progression. Understanding the underlying pathophysiological mechanisms of these combined exposures may support the development of more comprehensive prevention and intervention strategies.